The impact of website quality on Muslim tourists’ intention to visit halal destinations - Hasyim, Fuad; Ramly, Arroyan (Alkasb: Journal of Islamic Economics, 2025)
This study examines the impact of website quality on Muslim tourists’ intention to visit halal destinations, mediated by e-trust, e-satisfaction, and perceived halalness. Integrating the IS Success Model and the Theory of Planned Behavior, the study surveyed 172 Muslim travelers and analyzed the data using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that website quality significantly enhances e-trust, e-satisfaction, and perceived halalness, which in turn positively influence intention to visit. Website quality also directly affects travel intentions, underscoring its persuasive role in digital engagement. The findings contribute to halal tourism research by validating perceived halalness as a distinct mediating factor and highlight the strategic importance of culturally and religiously attuned digital platforms. Future research is encouraged to adopt longitudinal methods and broader cultural comparisons to deepen the understanding of Muslim travelers' digital behavior.